2010
DOI: 10.3402/nano.v1i0.5358
|View full text |Cite
|
Sign up to set email alerts
|

Potential toxicity of superparamagnetic iron oxide nanoparticles (SPION)

Abstract: Superparamagnetic iron oxide nanoparticles (SPION) are being widely used for various biomedical applications, for example, magnetic resonance imaging, targeted delivery of drugs or genes, and in hyperthermia. Although, the potential benefits of SPION are considerable, there is a distinct need to identify any potential cellular damage associated with these nanoparticles. Besides focussing on cytotoxicity, the most commonly used determinant of toxicity as a result of exposure to SPION, this review also mentions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
688
1
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 952 publications
(710 citation statements)
references
References 105 publications
(133 reference statements)
9
688
1
12
Order By: Relevance
“…4C). Nanoparticles also affect cell cycle progression [5,6], which is closely related to cell uptake of MNP [49]. Cytometric analysis of the cell cycle showed that 100 µM BPA led to an increase in the sub-G1 population (>40%) and a decrease in G0-G1 (∼30%) and S (∼10%) populations compared to untreated controls (Fig.…”
Section: In Vitro Dmsa-mnp Cytotoxicitymentioning
confidence: 92%
See 1 more Smart Citation
“…4C). Nanoparticles also affect cell cycle progression [5,6], which is closely related to cell uptake of MNP [49]. Cytometric analysis of the cell cycle showed that 100 µM BPA led to an increase in the sub-G1 population (>40%) and a decrease in G0-G1 (∼30%) and S (∼10%) populations compared to untreated controls (Fig.…”
Section: In Vitro Dmsa-mnp Cytotoxicitymentioning
confidence: 92%
“…Nanomaterials have a high surface/volume ratio, rendering them very reactive, and allows their accumulation within cells or tissues [5,6]. This reactivity can lead to toxicity due to interaction between nanomaterials and biological components [7].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this iron overload may lead to adverse biological effects such as inflammation, the formation of apoptotic bodies, impaired mitochondrial function (MTT), membrane leakage of lactate dehydrogenase (LDH assay), generation of ROS, increase in micronuclei (indicators of gross chromosomal damage; a measure of genotoxicity), and chromosome condensation. [599] …”
Section: Toxicity Concerns Of Mnpsmentioning
confidence: 99%
“…In particular, the excellent properties of Fe 3 O 4 -NPs give rise to numerous multitask applications including Magnetic Resonance Imaging (MRI) contrast agents, multimodal imaging, ferrofluid technology for thermotherapy, targeted drug delivery, cancer tumor detection via magnetometry, gene therapy, biomolecular separation, in vivo biomolecular detection, and tissue repair (Deng et al, 2014;Wu et al, 2013;Singh et al, 2010).…”
Section: Iron Oxide Nanoparticles (Magnetic Nanoparticles)mentioning
confidence: 99%
“…However, once the engineered Fe 3 O 4 -NPs are inside the cells, the coating is likely digested leaving bare particles exposed to cellular components and organelles thereby potentially influencing the overall integrity of the cells. Fe 3 O 4 -NPs with appropriate surface chemistry exhibit many interesting properties that can be exploited in a variety of biomedical applications such as MRI contrast enhancement, tissue repair, hyperthermia, drug delivery and in cell separation (Mahdavi et al, 2013;Singh et al, 2010).…”
Section: Iron Oxide Nanoparticles (Magnetic Nanoparticles)mentioning
confidence: 99%